2013
DOI: 10.1038/onc.2013.75
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell RelA/p65 promotes lung cancer proliferation through Wnt/β-catenin signaling in murine and human tumor cells

Abstract: Smoking is the most important risk factor for both lung cancer (LC) and chronic obstructive pulmonary disease. The aim of this study was to investigate the role of myeloid cell nuclear factor-κB in the regulation of tumor cell growth signaling. We subjected mice lacking myeloid RelA/p65 (rela(Δ-/-)) to a metastatic LC model. Cigarette smoke (CS) exposure significantly increased the proliferation of Lewis lung carcinoma cell tumors in wild-type mice. In CS-exposed rela(Δ-/-) mice, the tumor growth was largely i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 50 publications
(62 reference statements)
2
60
0
Order By: Relevance
“…The number of CRAMPpositive myeloid cells was significantly decreased in the tumor tissue of rela D À / À mice, while the total number of myeloid cells in the tumor tissue was unchanged. 27 The NF-kB signaling pathway has an important role in the regulation of cathelicidin. Inhibition of NF-kB by small interfering RNA and overexpression of IkBa reduced both basal and induced levels of Camp mRNA in murine mast cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of CRAMPpositive myeloid cells was significantly decreased in the tumor tissue of rela D À / À mice, while the total number of myeloid cells in the tumor tissue was unchanged. 27 The NF-kB signaling pathway has an important role in the regulation of cathelicidin. Inhibition of NF-kB by small interfering RNA and overexpression of IkBa reduced both basal and induced levels of Camp mRNA in murine mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…As shown earlier, the influx of macrophages and neutrophils in smoke-exposed lungs depends on myeloid p65/RelA. 27 We compared the relative CRAMP mRNA expression in the lungs of air and CS-exposed mice.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that CS-induced and tumorassociated inflammation in the tumor microenvironment promote LC growth via the release of inflammatory mediators by inflammatory cells (12,14,15,31). We and the Karin group showed that the nuclear factor-B (NF-B) pathway in myeloid cells is a key regulator of CS-promoted LC development in metastatic LC and K-ras-induced mouse models.…”
mentioning
confidence: 97%
“…Preclinical and clinical studies suggest that there is a causal relation between inflammation and LC development (12,14,15,22,31,33). Studies showed that CS-induced and tumorassociated inflammation in the tumor microenvironment promote LC growth via the release of inflammatory mediators by inflammatory cells (12,14,15,31).…”
mentioning
confidence: 98%
“…In addition, GSK3β was a phosphorylation substrate of Akt 17. Activation of Akt promoted the phosphorylation of GSK3β at Ser9, which in turn inhibited the degradation of β‐catenin and activated Wnt/β‐catenin signaling pathway 31. In this study, we found that IQUB overexpression increased the expression of p‐Akt, p‐GSK3β, and inhibited p‐β‐catenin, whereas IQUB knockdown showed the opposite effect.…”
Section: Discussionmentioning
confidence: 52%